2021
DOI: 10.2106/jbjs.oa.21.00013
|View full text |Cite
|
Sign up to set email alerts
|

Power-Tool Use in Orthopaedic Surgery

Abstract: Background:Power tools are an integral part of orthopaedic surgery but have the capacity to cause iatrogenic injury. With this systematic review, we aimed to investigate the prevalence of iatrogenic injury due to the use of power tools in orthopaedic surgery and to discuss the current methods that can be used to reduce injury.Methods:We performed a systematic review of English-language studies related to power tools and iatrogenic injuries using a keyword search in MEDLINE, Embase, PubMed, and Scopus databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In 1892, the motor-powered osteotome was introduced into clinical practice, followed by the powered circular and oscillating saw by the early 1900s 9 . The development of powered tools used as surgical instruments greatly improved overall clinical outcomes in orthopaedic surgery 10 . In rTHA specifically, extracting a well-fixed acetabular implant in a timely and safe manner is necessary to correct the underlying biomechanical or disease process.…”
Section: Acetabular Component Removal Systemsmentioning
confidence: 99%
“…In 1892, the motor-powered osteotome was introduced into clinical practice, followed by the powered circular and oscillating saw by the early 1900s 9 . The development of powered tools used as surgical instruments greatly improved overall clinical outcomes in orthopaedic surgery 10 . In rTHA specifically, extracting a well-fixed acetabular implant in a timely and safe manner is necessary to correct the underlying biomechanical or disease process.…”
Section: Acetabular Component Removal Systemsmentioning
confidence: 99%
“…Spine surgery itself commonly involves power driven tools and impact devices to decompress neurologic structures or mobilize bony anatomy. These tools are an integral part of spine surgery but have potential to cause iatrogenic injury to the patient, OR staff, and surgeons [10] . Overall, there is limited understanding of the possible significant exposure to occupational sound pollution in the operating suite.…”
Section: Introductionmentioning
confidence: 99%
“…While there are few papers examining prevalence of iatrogenic drill penetration injury, it seems to occur in approximately 0.1–0.49 % of cases [ 2 ]. However, many orthopedic studies have reported cases of iatrogenic drill penetration causing soft tissue injury.…”
Section: Introductionmentioning
confidence: 99%